Completion of a new national geological map series – the QMAP project - Rattenbury, Mark (New Zealand Science Review, 2012)
​Geological maps provide a fundamental resource that underpins geoscience research and is widely applied into New Zealand industry and society. GNS Science and its New Zealand Geo-logical Survey predecessor have been making geological maps of New Zealand for almost 150 years. The maps reflect the stored knowledge and the paradigms of their generation; they are interpretations based on observation and they are the testing grounds of geological concepts and process-related hypotheses. As such, geological maps have a shelf life. Continued data collection coupled with evolving ideas will render existing geological maps increasingly obsolete with time. From 1956 until 1968 the New Zealand Geological Survey devoted most of its available resources to the production of a series of 1:250 000 geological maps covering all of the country. Known informally as the “4-mile” series (four miles to the inch, approximating the published scale), the map series was a triumph in that it portrayed regional New Zealand geology with uniformity and a consistent mapping philosophy. The series served science and other end-user needs well for several decades but, by the 1980s, amidst a highly productive period of research by government, academic and industry geologists, and the embracing of plate tectonic theory amongst others, these maps were becoming noticeably outdated.